Wearable thermoelectric 3D spacer fabric containing a photothermal ZrC layer with improved power generation efficiency. (1st September 2021) - Li, Mufang; Chen, Jiaxin; Luo, Mengying; Zhong, Weibing; Wang, Wen; Qing, Xing; Lu, Ying; Yang, Liyan; Liu, Qiongzhen; Wang, Yuedan; Wang, Dong
Graphical abstract: Highlights: ZrC-PPSF was prepared with improved thermoelectric power generation efficiency. A larger ΔT generated and maintained between the two sides of ZrC-PPSF. The light absorption capacity of ZrC-PPSF is as high as 99.95%. The voltage generated under sunshine is 11 times the voltage generated indoors. Abstract: Harvesting energy directly from the body heat has been suggested as an effective way to realize sustainably and uninterruptedly wearable power supply. However, the low temperature gradient (ΔT) between the human body and the environment has limited the power generation efficiency. In this study, the photothermal-thermoelectric 3D spacer fabric (ZrC-PPSF) was prepared by coating a thin zirconium carbide/polyurethane (ZrC/PU) photo-thermal layer on the poly (3, 4-ethylenedioxythiophene):poly (styrenesulfonate) (PEDOT:PSS)/spacer fabric (SF) thermoelectric composite (PPSF). By utilizing the excellent photo-thermal conversion of ZrC and the thermal insulation performance of PPSF, a larger ΔT was generated and maintained, so as to enhance the power generated and efficiency. The effects of ZrC concentration, SF thickness and optical power density on the photo-thermal efficiency and voltage generated were studied. When the ZrC concentraiton is 1.5 wt%, the ΔT increases form 67.5 °C to 179.3 °C under the optical power density of 500 mW/cm 2 . Regardless of sunny and cloudy day, a larger ΔT can be generated. Based on this, a flexible and wearable wristband containing 30 ZrC-PPSF units was prepared. Encouragingly, the voltage generated by the wristband under the sunshine is almost 11 times the voltage generated indoors. Under the optical density of 100 mW/cm 2 for 800 min, the highest voltage generated by the wristband is 9.11 mV, much higher than the 3.12 mV generated without light. All the results demonstrate that it is a very effective and simple method to improve the thermoelectric power generation efficiency by photo-thermal conversion. The wearable TE device prepared in this study is especially suitable for outdoor application, and provide continuous and stable energy for the wearable electronics.